2018
DOI: 10.1186/s12887-018-1017-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal socio-demographic and psychological predictors for risk of developmental delays among young children in Mongolia

Abstract: BackgroundFactors influencing child development are not well studied in developing settings, and especially in Mongolia. This cohort study examined the relationship between maternal socio-demographic and psychological conditions on risk of young child developmental delay.MethodsA total of 150 children aged between 13 ~ 24 months old participated in this study. The participants were randomly selected from a pre-existing cohort of 1297 children who were involved in a study on infant bilirubin nomogram developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
6
0
2
Order By: Relevance
“…The present study assessed selected risk factors of DD in infants with the results mostly supporting previous findings from other countries, both in the European region and outside of Europe, and reinforcing the multiple etiology of DD [1,2,4,9,15,18,19,27,32]. Preventive strategies regarding DD in Polish infants should focus on the pre-, peri- and postnatal risk factors identified in this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study assessed selected risk factors of DD in infants with the results mostly supporting previous findings from other countries, both in the European region and outside of Europe, and reinforcing the multiple etiology of DD [1,2,4,9,15,18,19,27,32]. Preventive strategies regarding DD in Polish infants should focus on the pre-, peri- and postnatal risk factors identified in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The risk factors for DD include maternal and infant biological, psychosocial (individual and familial), and environmental factors. In the period before birth, such factors as young maternal age [9,10,11], short interval between pregnancies, history of previous abortion [11], multiple gestation [1,4], preeclampsia, placental abruption, immaturity and intrauterine growth restriction [11], a mother’s underlying diseases (including multi-morbidity [4,12] and addiction), being deprived of primary care during pregnancy, low maternal educational level [2,9], and being a single mother household [2,4] are considered to increase the risk of DD in the infant. Delivery through caesarian section [11] and preterm birth [1,13,14,15,16] are the most important risk factors of DD in the perinatal period, and male gender [4,9,13], low birth weight [1,2,4], first minute Apgar score <7 [11], intracranial hemorrhage [17], kernicterus, and no breastfeeding [1] are all risk factors in the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, girls scored higher than boys in the problem-solving domain, as did the study by El-Ella which showed that girls had higher scores compared to boys for communication and problemsolving domains. (10) While some studies (15) reported no gender difference when it comes to childhood development, some studies (16) showed the reverse; boys had a higher total developmental score than girls. In the current study children born first to the third order of birth have higher social score .These findings agree with a study in Iran that concluded that developmental delay is more prevalent in children with higher order of birth.…”
Section: Discussionmentioning
confidence: 99%
“…Esto afecta a los países en desarrollo, debido a que el mantenimiento de estos niños con discapacidades resultan en gastos, lo cuales no siempre pueden ser solventados en su totalidad, ya que los más afectados en la mayor parte de los casos son las personas de bajos recursos, como lo demuestra un estudio realizado por Gwatkin 17 en donde se evaluaron 56 casos, determinándose que los niños provenientes de familias de bajos recursos aumentan sus impedimentos cognitivos, contribuidos por el ambiente de pobreza al que están expuestos 18 . La prevalencia de retraso global del neurodesarrollo puede deberse a las características sociodemográficas de la población que es atendida, debido a la relación de dicha patología con el entorno familiar y ambiental al cual es expuesto el infante causando los efectos deletéreos en la adquisición de los hitos de desarrollo [19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionunclassified
“…Cabe destacar que el retraso global del neurodesarrollo, la parálisis cerebral y la discapacidad cognitiva fueron los trastornos del desarrollo más frecuente evidenciados, siendo este grupo de trastornos los que presentan mayor cantidad de factores de riesgo biológicos y ambientales que pueden ser modificados para disminuir su incidencia en la población, además de que los mismos guardan relación con las características sociodemográficas de la población [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Discussionunclassified